(3EOGQI GdGfJGL hGdYedjGJs - (3SejQ(B, (3Ndjds ((3YeGf(B:s (3OGQ GSGeI ddfTQ h GdJhRjY(B,s, 2009)
(3eGgjI GdGfJGL , fXGe JcGdja GdGfJGLjI , eGgjI GdBjRh h GdLhOI GdTGedI , GdNWhGJ GdJfajPjI dYedjI JMSjf GdLhOI h GdGfJGLjI , EOGQI GdeNRhf , GdJNWjW h GdJbjje h GdgjcdI ddeTGQjY , eGgjI EOGQI GdYedjGJ , GSJQGJjLjI GdYedjGJ , GdJNWjW h GdJfHD HGdWdH aj GOGQI GdYedjGJ , GdWGbI GdYedjGJjI , GNJjGQ GdefJhL h JUejeg , bjGS GdYed h Jbjje GdCOGA GdeDSSj, GdYedjGJ GdeUQajI GdGdcJQhfjI (B.s
(3eQGLY(B197(3U(B.s
Keywords: (3EOGQI GdCYeGds; (3EOGQI GdGfJGLs; (3GdEjRhs; (3VHW GdLhOIs